2002
DOI: 10.1002/ecjb.10020
|View full text |Cite
|
Sign up to set email alerts
|

A Λ‐type neuron model using enhancement‐mode MOSFETs

Abstract: SUMMARYRecently, research has been actively pursued to implement a neuron, which is the basic unit for building neural networks, in hardware with engineering applications as the objective. Specifically, pulse-type hardware neuron models, which approximately replicate pulse signals, have been examined as the information transmission stage in the brain. However, a pulse-type hardware neuron model is a complex circuit and includes inductors. Consequently, there are few practical models. In this paper, we present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 8 publications
0
13
0
Order By: Relevance
“…A + and A -, which are both positive, determine the maximum amounts of synaptic modification, which occur when Δt is close to zero. To correspond to the continuous firing patterns which the P-HNM outputs, Song's STDP rule was converted into equations (6) - (8).…”
Section: B Stdpmentioning
confidence: 99%
See 1 more Smart Citation
“…A + and A -, which are both positive, determine the maximum amounts of synaptic modification, which occur when Δt is close to zero. To correspond to the continuous firing patterns which the P-HNM outputs, Song's STDP rule was converted into equations (6) - (8).…”
Section: B Stdpmentioning
confidence: 99%
“…On the other hand, we proposed a pulse-type hardware neuron model (P-HNM) that approximately simulates pulse signal as the information transmission means in the brain [8].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Sekine et al proposed a Bonhoefer-van der Pol (BVP) equivalent model [30], which is based on negative differential resistance of a FET circuitry called a lambda transistor. It is also shown that some extensions of this model result in bursting action potentials and chaotic responses [31]- [35]. The BVP model is based on the Hodgkin-Huxley equations and is reduced to two dimensions focusing on qualitative description of nerve dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in these days, the studies on CA2 region in hippocampus, which is difficult to study because its existence domain is very small, has been proceeded [6,7]. For construction of a model with the features of cell body in living body, the cell body model using Λ-type negative resistance elements can be constructed with simple circuits [8][9][10]. However, currently, the analysis cannot be conducted for large scale of NN analysis because of numerous parameters.…”
Section: Introductionmentioning
confidence: 99%